Co-combustion characteristics and kinetic analysis of three different wastes of antibiotic fermentation and coal. Issue 8 (17th March 2023) - Yuan, Guanglei; Liang, Ruru; Duan, Erhong; Liu, Renping
Abstract : The combustion characteristics and kinetic properties of three antibiotic residues and their mixtures with coal were studied by thermogravimetric-differential scanning calorimetry (TG-DSC), and the kinetic mechanism functions were calculated. Abstract : This study uses thermogravimetric analysis to investigate the combustion characteristics and kinetics of three kinds of antibiotic fermentation residue (penicillin residue, streptomycin residue and cephalosporin residue), which were blended with a kind of Chinese coal. The kinetic parameters were estimated in terms of the Flynn–Wall–Ozawa (FWO) and Vyazovkin (V) methods, and the kinetic mechanism function was solved using the integral master-plot method. The experiments were carried under an air atmosphere of 40 mL min −1 at heating rates of 10, 15, 20, 25 and 30 °C min −1, and the comprehensive combustion characteristic index ( S N ) was introduced to evaluate the combustion performance. The results indicated that the combustion characteristic parameters of coal blended with 10–40% antibiotic fermentation residues (AFRs) were enhanced, and there was an especially dramatic rise in the comprehensive combustion index. There were synergistic effects in every blend, with negative effects occurring at temperatures between 200 and 450 °C and with positive effects during the char oxidation period. For streptomycin residue, the lowest average activation energy of the blends was obtained at a 20% blending ratio. For the penicillin residue, the lowest average activation energy of the blends was at 10% and it was at the same percentage (10%) for the cephalosporin residue. The integral master-plot method was utilized to determine the appropriate kinetic model of combustion for the blends.